Differences in oxidative stress status and expression of MKP-1 in dorsal medulla of transgenic rats with altered brain renin-angiotensin system - Nautiyal, Manisha (American Physiological Society, 2012)
ANG II-stimulated production of reactive oxygen species (ROS) through NADPH oxidase is suggested to activate MAPK pathways, which are implicated in neurally mediated pressor effects of ANG II. Emerging evidence suggests that ANG-(1–7) up regulates MAPK phosphatases to reduce MAPK signaling and attenuate actions of ANG II. Whether angiotensin peptides participate in long-term regulation of these systems in the brain is not known. Therefore, we determined tissue and mitochondrial ROS, as well as expression and activity of MAPK phosphatase-1 (MKP-1) in brain dorsal medullary tissue of hypertensive transgenic (mRen2)27 rats exhibiting higher ANG II/ANG-(1–7) tone or hypotensive transgenic rats with targeted decreased glial expression of angiotensinogen, ASrAOGEN (AS) exhibiting lower ANG II/ANG-(1–7) tone compared with normotensive Sprague-Dawley (SD) rats that serve as the control strain. Transgenic (mRen2)27 rats showed higher medullary tissue NADPH oxidase activity and dihydroethidium fluorescence in isolated mitochondria vs. SD or AS rats. Mitochondrial uncoupling protein 2 was lower in AS and unchanged in (mRen2)27 compared with SD rats. MKP-1 mRNA and protein expression were higher in AS and unchanged in (mRen2)27 compared with SD rats. AS rats also had lower phosphorylated ERK1/2 and JNK consistent with higher MKP-1 activity. Thus, an altered brain renin-angiotensin system influences oxidative stress status and regulates MKP-1 expression. However, there is a dissociation between these effects and the hemodynamic profiles. Higher ROS was associated with hypertension in (mRen2)27 and normal MKP-1, whereas the higher MKP-1 was associated with hypotension in AS, where ROS was normal relative to SD rats.